Characterization of Serologically Nontypeable Actinobacillus actinomycetemcomitans Isolates - Paju, Susanna (American Society for Microbiology, 1998)
Our previous studies have shown that Actinobacillus actinomycetemcomitans isolates of a given arbitrarily primed PCR (AP-PCR) genotype belong to the same serotype (of serotypes a through e). In the present study we investigated whether the AP-PCR genotypes of nonserotypeable A. actinomycetemcomitans isolates match those of the serotypeable isolates. The isolates were additionally characterized by restriction analysis of the apaH PCR amplification products. The material included 75 nonserotypeable and 18 serotypeable A. actinomycetemcomitans isolates from 34 epidemiologically unrelated subjects. The serotypeable isolates were obtained from subjects who also harbored nonserotypeable isolates. Eight AP-PCR genotypes were distinguished among the isolates; six genotypes matched those detected in our previous studies, whereas two genotypes were new. Intraindividually, the A. actinomycetemcomitans isolates produced identical AP-PCR banding patterns, regardless of whether they were serotypeable or nonserotypeable, in 22 of 23 subjects participating with multiple isolates. AP-PCR genotype 3, corresponding to serotype c, was by far the most common among the nonserotypeable isolates (62% of subjects). Results obtained with the apaH restriction analysis confirmed the results obtained with AP-PCR for 31 of the 34 subjects. The results suggest that nonserotypeable A. actinomycetemcomitans isolates originate from serotypeable isolates, especially from serotype c isolates, and the likelihood of the existence of additional serotypes is small.